2022
DOI: 10.1002/star.202200133
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Films from Spray Dried Starch Inclusion Complexes with Bioactive Compounds—The Effect of Glycerol and pH

Abstract: In the present study, thermoplastic films are prepared using spray dried starch-bioactive compound systems powders with different concentrations of glycerol (20% or 40%). The starch-based films are produced by casting after dissolution under neutral (pH 7) or alkaline conditions (pH 12). Results reveal that elevated glycerol contents lead to increased moisture and hygroscopicity which is related to the availability of more ─OH groups. ANOVA shows that the glycerol concentration, the pH value, and the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…[13] Studies found that pH modification could affect the amylose content and granular structure of starch, [14][15][16][17] resulting in the improvement in mechanical properties and water resistance properties of starch-based films. [9,18,19] The solution, size, and distribution pattern of proteins depend on the pH conditions, which have an important impact on the properties of protein-based films. [10,13,20] Although the effect of pH on the compatibility between starch and protein has been reported, [21,22] it is not clear that adjusting the pH can influence the performance of films composited of starch and protein.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Studies found that pH modification could affect the amylose content and granular structure of starch, [14][15][16][17] resulting in the improvement in mechanical properties and water resistance properties of starch-based films. [9,18,19] The solution, size, and distribution pattern of proteins depend on the pH conditions, which have an important impact on the properties of protein-based films. [10,13,20] Although the effect of pH on the compatibility between starch and protein has been reported, [21,22] it is not clear that adjusting the pH can influence the performance of films composited of starch and protein.…”
Section: Introductionmentioning
confidence: 99%